ONLINE GAMING INTENSITY AND VERBAL AGGRESSIVE BEHAVIOR AMONG ADOLESCENTS: EVIDENCE OF A MODERATE POSITIVE CORRELATION - Abdurrahman, Abdurrahman (LPPM Universitas Jambi, 2026)
The rapid growth of digital media exposure has transformed adolescents’ daily interactions, particularly through online gaming. While prior studies have explored gaming and aggression, limited research has specifically examined verbal aggressive behavior within Junior High School settings. This study investigates the relationship between online game usage and verbal aggressive behavior among adolescents in a Junior High School context and identifies its educational implications for school-based behavior management. A quantitative correlational design with a cross-sectional approach was employed. The participants consisted of 60 eighth-grade students at a Junior High School during the 2024/2025 academic year. Data were collected using validated Likert-scale questionnaires measuring online game usage intensity and verbal aggressive behavior. Instrument validity was confirmed using Corrected Item Total Correlation, and reliability analysis yielded Cronbach’s Alpha coefficients of 0.898 (online game usage) and 0.880 (verbal aggressive behavior). Data were analyzed using the Pearson Product Moment correlation test at a significance level of 0.05. The analysis revealed a moderate and statistically significant positive correlation between online game usage and verbal aggressive behavior (r = 0.534, p < 0.05). The findings indicate that higher gaming intensity is associated with increased tendencies toward verbal aggression, including shouting, arguing, and using harsh language. This study contributes novelty by specifically focusing on verbal aggression in Junior High School adolescents within the context of digital media exposure. The results suggest that online gaming intensity is a meaningful predictor of school-based behavior patterns.